COMPARATIVE ANALYSIS OF SEMANTIC SHIFTS IN ENGLISH AND UZBEK MEDICAL TERMINOLOGY - Salikhova Nodira Nurullayevna (International Journal of Literature and Language Studies, 2026)
This article examines semantic shifts in English and Uzbek medical terminology, focusing on how specialist meanings expand, narrow, or reframe across time and through translation. The study aims to compare mechanisms of change such as metaphorization, metonymy, eponymization, and internationalization, and to identify how these processes interact with borrowing and standardization in two structurally different languages. The methodology combines corpus informed qualitative analysis with a structured classification of shift types in a bilingual dataset of clinical and educational terms, complemented by dictionary triangulation and contextual verification in patient oriented and professional genres. Scientific novelty lies in a unified comparative typology that links shift direction to term formation patterns and to register pressures, showing where Uzbek calques stabilize meaning and where English polysemy drives divergence.